Steel plates, components, and methods of manufacturing them

KR103018280B1Active Publication Date: 2026-09-11JFE STEEL CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
KR1020247005333
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-08-31
Filing Date
2022-08-15
Publication Date
2026-09-11
Estimated Expiration
2042-08-15

Smart Images

  • Figure 112024017731076-PCT00004_ABST
    Figure 112024017731076-PCT00004_ABST
Patent Text Reader

Abstract

Provides steel plates, members, and methods for manufacturing the same having high strength, high ductility, excellent elongation flange formability, and a high work hardening index. It has a steel microstructure having a composition in mass% of C: 0.06–0.25%, Si: 0.4–2.5%, Mn: 1.5–3.5%, P: 0.02% or less, S: 0.01% or less, sol.Al: less than 1.0%, N: less than 0.015%, with the remainder being Fe and unavoidable impurities, and in area percentage, polygonal ferrite: 10% or less (including 0%), tempered martensite: 30% or more, fresh martensite: 20% or less (including 0%), lower bainite: 5–50%, and in volume percentage, retained austenite: 5–20%, and SC≥0.5 / SC≥0.3×100 Steel plate with 15% or more.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to a steel plate used in various applications such as automobiles and home appliances, a component using the steel plate, and a method for manufacturing the same. Background Technology

[0002] Recently, as the demand for lightweighting of automobile bodies has increased, the application of high-strength steel sheets with a strength of 980 to 1180 MPa to automobile frame parts and seat parts is progressing. However, when high-strength steel sheets with a strength of 980 to 1180 MPa are applied to automobile parts, press cracks are prone to occur due to a decrease in ductility or a decrease in elongation flange formability. For this reason, these high-strength steel sheets are required to have excellent formability compared to conventional ones.

[0003] Against this backdrop, TRIP steel, in which residual γ is dispersed in the microstructure of the steel sheet, has been developed as a technology to improve the ductility of the steel sheet.

[0004] For example, Patent Document 1 describes a steel containing C: 0.10 to 0.45%, Si: 0.5 to 1.8%, and Mn: 0.5 to 3.0%, which is aged at 350 to 500°C for 1 to 30 minutes after annealing to generate residual γ, thereby producing a TS (tensile strength) of 80 kgf / mm² 2 Ideal and TS×El ≥ 2500 kgf / mm 2 It has been disclosed that a steel plate having high ductility of 1% is obtained.

[0005] Patent Document 2 discloses that a steel sheet with excellent ductility: El and elongation flange formability: λ is obtained by cooling a steel containing C: 0.10 to 0.25%, Si: 1.0 to 2.0%, and Mn: 1.5 to 3.0% at a rate of 10°C / s or more after annealing to 450 to 300°C and maintaining it for 180 to 600 seconds, thereby controlling the retained austenite to 5% or more, bainitic ferrite to 60% or more, and polygonal ferrite to 20% or less by the drop rate.

[0006] Patent Document 3 discloses that by cooling a steel sheet having a specific composition to a temperature range of 150 to 350°C after annealing, and then reheating and maintaining it at 350 to 600°C, a structure containing ferrite, tempered martensite, and retained austenite is obtained, thereby imparting high ductility and high elongation flange formability to the steel sheet. This utilizes the principle known as Q&P (Quenching & Partitioning), which involves cooling the steel to a temperature range between the martensite transformation start temperature (Ms point) and the martensite transformation completion temperature (Mf point) during the cooling process, and then reheating and maintaining it to stabilize the retained γ. Recently, the development of high-strength steel with high ductility and high elongation flange formability has been progressing through the use of this principle.

[0007] Patent Document 4 discloses a method that improves upon the above Q&P treatment. That is, a steel having a specific composition is annealed at a temperature of Ae3 point - 10°C or higher to reduce the polygonal ferrite content to 5% or less, and then cooling is stopped at a relatively high temperature of Ms - 10°C to Ms - 100°C, thereby generating upper bainite when reheated to 350 to 450°C, thereby obtaining high ductility and high elongation flange formability.

[0008] In addition, Patent Document 5 discloses a method for obtaining a steel sheet with excellent ductility and low-temperature toughness by utilizing bainite generated at low temperatures and bainite generated at high temperatures. That is, after annealing steel containing C: 0.10 to 0.5%, the steel is cooled to 150 to 400°C at a cooling rate of 10°C / s or more and maintained at that temperature range for 10 to 200 seconds to generate bainite in the low-temperature range, and then reheated to a temperature range of 400°C to 540°C or less and maintained at that temperature range for 50 seconds or more to generate bainite in the high-temperature range, thereby obtaining a steel sheet with excellent ductility and low-temperature toughness. Prior art literature

[0009] Japanese Patent Publication No. Hei 6-35619, Japanese Patent No. 4411221, Japanese Patent No. 5463685, Japanese Patent No. 5780086, Japanese Patent No. 5728115 The problem to be solved

[0010] However, the conventional TRIP steel described in Patent Document 1 had the problem that although it had excellent ductility, its elongation flange formability was very low.

[0011] In the technology described in Patent Document 2, bainitic ferrite is mainly utilized as a microstructure and the ferrite content is kept low, so while the elongation flange formability is excellent, the ductility is not necessarily high. For this reason, additional improvement in ductility was required when considering adaptation to difficult-to-form parts.

[0012] The technology described in Patent Document 3 achieves relatively high ductility and high elongation flange formability compared to conventional TRIP steel or steel utilizing bainitic ferrite. However, fracture was observed during forming of difficult-to-form parts such as center pillars, requiring further improvement in ductility. It became clear that in steel sheets to which this technology is applied, the work hardening index (n value), which is an indicator of the work hardening rate and has a good correlation with elongation formability, is not necessarily sufficient.

[0013] In the technology described in Patent Document 4, the amount of polygonal ferrite produced is reduced in order to reduce massive martensite, so sufficient ductility cannot be secured. In addition, the cooling stop temperature is set relatively high to improve El, and since a large amount of untransformed γ remains at the time of cooling stop, massive martensite is likely to remain.

[0014] In the technology described in Patent Document 5, low-temperature reverse transformation bainite and high-temperature reverse transformation bainite are utilized to improve ductility, but bainite that transforms at low temperatures contributes little to the improvement of ductility, and when bainite generated at high temperatures is used, massive structures tend to remain. For this reason, it is difficult to simultaneously impart high ductility and high elongation flange formability.

[0015] As such, in conventional technology, a steel sheet having sufficiently high ductility, high elongation flange formability, and a high work hardening index was not obtained.

[0016] The present invention is made to solve these problems and aims to provide a steel plate, a member, and a method for manufacturing them, having a tensile strength of 980 MPa or more, high ductility and excellent elongation flange formability, and furthermore, a high work hardening index.

[0017] In addition, the term "steel sheet" as used herein includes galvanized steel sheets with a surface that has undergone zinc plating treatment.

[0018] In the present invention, a tensile strength of 980 MPa or more refers to a tensile strength of 980 MPa or more in accordance with JIS Z2241.

[0019] In addition, high ductility means that the total elongation T-El is 16.0% or more for TS: less than 1180 MPa, 14.0% or more for TS: 1180 MPa or more and less than 1320 MPa, and 13.0% or more for TS: 1320 MPa or more.

[0020] In addition, excellent elongation flange formability refers to a case where, after punching a sample of 100 mm × 100 mm square size using a punching tool with a punch diameter of 10 mm and a die diameter of 10.3 mm (clearance 13%), a conical punch with a tip angle of 60 degrees is used to expand the hole until a crack penetrating the plate thickness occurs, with d0 being the initial hole diameter (mm) and d being the hole diameter at the time of crack occurrence (mm), and the hole expansion rate λ (%) = {(d-d0) / d0}×100 is 30% or more.

[0021] In addition, a high work hardening index indicates that, in accordance with JIS Z2253, the value of n obtained from two points where the nominal strain on the nominal stress-nominal strain curve is 2% and 5% is 0.130 or higher for TS: less than 1180 MPa, 0.070 or higher for TS: 1180 MPa or higher but less than 1320 MPa, and 0.060 or higher for TS: 1320 MPa or higher. means of solving the problem

[0022] The inventors have carefully examined means for providing high ductility, excellent elongation flange formability, and a high work hardening index, and have obtained the following conclusions.

[0023] (i) After hot rolling and cold rolling a steel slab having a predetermined composition, the annealing temperature is maintained at 810 to 900 ℃, and the temperature range from 810 ℃ to the martensite transformation start temperature Ms is cooled at an average cooling rate (CR1) of 5 to 100 ℃ / s, thereby controlling the polygonal ferrite to 10% or less in order to secure a predetermined residual γ in the final structure.

[0024] (ii) During the cooling process following the holding in the annealing process, the temperature range from the martensite transformation initiation temperature Ms to the residence stop temperature (T1) (°C) is maintained at an average cooling rate (CR2) of 10°C / s or less and a residence time t of 5 s or more and 60 s or less, thereby generating some martensite and then bainite. During the intermediate holding in this temperature range, the bainite transformation is accelerated by nucleating the martensite, thereby generating lower bainite, which contributes to the improvement of the strength-ductility balance and work hardening index, and retained austenite (retained γ), which contributes to the improvement of ductility in the final structure.

[0025] (iii) In the unregenerated γ region of the remainder, before carbon enrichment up to T0 composition, which causes massive tissue formation occurs, the temperature range from the retention stop temperature (T1) (°C) to the cooling stop temperature (T2) (°C) of 180°C or higher and less than 290°C is rapidly cooled at an average cooling rate (CR3) of 3 to 100°C / s, and the unregenerated γ region of the remainder is divided by martensitic transformation or lower bainite transformation, thereby dispersing the residual γ and reducing the massive tissue.

[0026] In addition, the massive structure here refers to fresh martensite or retained austenite that appears massive on an SEM. Also, the T0 composition refers to a composition in which the free energies of austenite and bainite become equal, and the bainite transformation stops.

[0027] (iv) Afterwards, by reheating the temperature range from the cooling stop temperature (T2) to 380 ℃ at an average heating rate of 2 ℃ / s or more, and maintaining the temperature range from 340 ℃ to 590 ℃ for 20 s or more and 3000 s or less, the martensite is converted into tempered martensite, and at the same time, carbon is distributed to the film-like residual γ formed in the lower bainite during the cooling period, thereby stabilizing the residual γ. In addition, by slow cooling at an average cooling rate (CR4) of 0.01 to 5 ℃ / s, the formation of a massive structure due to excessive C distribution to the residual γ is suppressed, and the elongation flangeability of the fresh martensite can be improved through self-tempering.

[0028] In this way, by utilizing the bainite transformation before the martensite transformation and also utilizing slow cooling after reheating, it becomes possible to achieve both stable utilization of residual γ and reduction of the massive structure, which has been difficult until now.

[0029] As a result, a steel plate having very high ductility, excellent elongation flange formability, and furthermore, a high work hardening index can be obtained. In addition, according to the present invention, it is also possible to increase the strength.

[0030] The present invention is based on the above findings and, specifically, provides the following.

[0031] [1] Mass %,

[0032] C : 0.06 ∼ 0.25 %,

[0033] Si : 0.4 ~ 2.5 %,

[0034] Mn : 1.5 ~ 3.5 %,

[0035] P : 0.001 ∼ 0.02 %,

[0036] S : 0.0001 ∼ 0.01 %,

[0037] sol.Al : 0.005% or more and less than 1.0%,

[0038] It has a composition containing N: 0.0001% or more and less than 0.015%, with the remainder consisting of Fe and unavoidable impurities, and

[0039] By area ratio,

[0040] Polygonal ferrite: 10% or less (including 0%), and

[0041] Tempered martensite: 30% or more, and

[0042] Fresh martensite: 20% or less (including 0%), and

[0043] Lower bainite: 5 to 50 percent, and

[0044] Having a steel microstructure with a volume percentage of retained austenite: 5 to 20 percent,

[0045] Area S of the region where the C concentration is 0.50% or higher C≥0.5 a, Area S of the region where the concentration of C is 0.30% or higher C≥0.3 The ratio S in C≥0.5 / S C≥0.3 Steel plate in which ×100 is 15% or more.

[0046] [2] The above composition of components is additionally in mass %,

[0047] Ti : 0.1% or less,

[0048] B: A steel plate described in [1] containing one or two types selected from 0.01% or less.

[0049] [3] The above composition of components is additionally in mass %,

[0050] Cu: 1% or less,

[0051] Ni: 1% or less,

[0052] Cr: 1.0% or less,

[0053] Mo: 0.5% or less,

[0054] V : 0.5% or less,

[0055] Nb : 0.1% or less,

[0056] Zr: 0.2% or less and

[0057] A steel plate described in [1] or [2] containing one or more types selected from W: 0.2% or less.

[0058] [4] The above composition of components is additionally in mass %,

[0059] Ca : 0.0040 % or less,

[0060] Ce : 0.0040 % or less,

[0061] La : 0.0040 % or less,

[0062] Mg: 0.0030% or less,

[0063] Sb: 0.1% or less and

[0064] A steel plate described in any one of [1] to [3] containing one or more types selected from Sn: 0.1% or less.

[0065] [5] A steel plate having a zinc plating layer on its surface, as described in any one of [1] to [4].

[0066] [6] A member made using a steel plate described in any one of [1] ~ [5].

[0067] [7] After performing hot rolling and cold rolling on a steel slab having a compositional composition described in any one of [1] to [4], annealing is performed on the obtained cold-rolled steel sheet, and

[0068] The above annealing is,

[0069] A process of holding at an annealing temperature of 810 to 900 ℃, and

[0070] A process for cooling the temperature range from 810 ℃ to the martensitic transformation initiation temperature Ms at an average cooling rate CR1: 5 to 100 ℃ / s, and

[0071] A process for retaining at a temperature range from a martensitic transformation initiation temperature Ms to a retention stop temperature T1: Ms-100 (℃) to Ms-10 (℃) for a retention time t: 5 s or more and 60 s or less at an average cooling rate CR2: 10 ℃ / s or less, and

[0072] A process for cooling the temperature range from the above residence stop temperature T1 to a cooling stop temperature T2 of 180 ℃ or higher and less than 290 ℃ at an average cooling rate CR3: 3 to 100 ℃ / s, and

[0073] A process of heating the temperature range from the above cooling stop temperature T2 to 380 ℃ at an average heating rate of 2 ℃ / s or more, and

[0074] A process of retaining at an average cooling rate CR4: 0.01 to 5 ℃ / s for a period of 20 s to 3000 s within a temperature range of 340 ℃ to 590 ℃, and

[0075] A method for manufacturing a steel plate, comprising a process of cooling to a temperature of 50 ℃ or lower at an average cooling rate CR5: 0.1 ℃ / s or higher.

[0076] [8] A method for manufacturing a steel plate as described in [7], wherein the steel plate is subjected to a process of maintaining the above average cooling rate CR4: 0.01 to 5 ℃ / s, and the steel plate is subjected to a hot-dip galvanizing treatment or an alloyed hot-dip galvanizing treatment.

[0077] [9] A method for manufacturing a steel plate as described in [7], comprising a process of electro-galvanizing the steel plate after cooling at an average cooling rate CR5: 0.1 ℃ / s or higher.

[0078]

[10] A method for manufacturing a member comprising a process of forming a member by performing at least one of forming and joining processes on a steel plate described in any one of [1] to [5]. Effects of the invention

[0079] According to the present invention, steel plates and components having very high ductility, excellent elongation flange formability, and furthermore, a high work hardening index can be obtained. In addition, according to the present invention, it is also possible to increase strength. When the steel plates of the present invention are applied to automotive parts, weight reduction of the automotive parts is realized, and an improvement in fuel efficiency is expected. Brief explanation of the drawing

[0080] Figure 1 is an example of an SEM image of the steel structure of a steel plate. FIG. 2 is a diagram illustrating a forma test for measuring the area ratio of tempered martensite and lower bainite in the steel structure of the present invention. FIG. 3 is a drawing for explaining the method of manufacturing a steel plate of the present invention. Specific details for implementing the invention

[0081] The present invention will be described in detail below. Furthermore, the present invention is not limited to the following embodiments.

[0082] The steel sheet of the present invention has a composition in mass% comprising C: 0.06 to 0.25%, Si: 0.4 to 2.5%, Mn: 1.5 to 3.5%, P: 0.02% or less, S: 0.01% or less, sol.Al: less than 1.0%, and N: less than 0.015%, with the remainder being Fe and unavoidable impurities; has a steel microstructure in area percentage comprising polygonal ferrite: 10% or less (including 0%), tempered martensite: 30% or more, fresh martensite: 20% or less (including 0%), lower bainite: 5 to 50%, and retained austenite: 5 to 20% in volume percentage, and has a C concentration of 0.50% Area S of the region that is ideal C≥0.5 a, Area S of the region where the concentration of C is 0.30% or higher C≥0.3 The ratio S in C≥0.5 / S C≥0.3 ×100 is 15% or more.

[0083] The steel plate of the present invention will be described below in the order of compositional components and steel structure.

[0084] The steel plate of the present invention contains the following components. In the following description, the unit of the component content, “%”, means “mass%”.

[0085] C : 0.06 ∼ 0.25 %

[0086] C is included from the perspective of securing a predetermined strength by securing the area ratio of tempered martensite, from the perspective of improving ductility by securing the volume ratio of residual γ, and from the perspective of improving ductility by stabilizing residual γ through concentration within it. Since the strength and ductility of the steel sheet cannot be sufficiently secured if the C content is less than 0.06%, the lower limit is set to 0.06%. Preferably, it is 0.09% or more, and more preferably 0.11% or more. If the content exceeds 0.25%, the lower bainite transformation during residence in the cooling process is delayed, making it difficult to form a film-like residual γ that is generated adjacent to a predetermined amount of lower bainite. As a result, ductility decreases. Furthermore, as the mass martensite or mass residual γ increases, the elongation flange formability deteriorates. In addition, various properties such as the spot weldability, bendability, and hole expandability of the steel sheet deteriorate significantly. For this reason, the upper limit of the C content is set to 0.25%. From the perspective of improving ductility and spot weldability, it is desirable to keep the C content at 0.22% or less. From the perspective of further improving ductility and spot weldability, it is more desirable to keep the C content at 0.20% or less.

[0087] Si : 0.4 ~ 2.5 %

[0088] Si is included from the perspective of strengthening ferrite to increase strength, and from the perspective of suppressing the formation of carbides within martensite or bainite to improve the stability of residual γ and thereby enhance ductility. From the perspective of suppressing the formation of carbides to improve ductility, the Si content should be 0.4% or more. From the perspective of improving ductility, it is preferable that the Si content be 0.6% or more. More preferably, the Si content is 0.8% or more. If the Si content exceeds 2.5%, the rolling load during hot rolling becomes extremely high, making it difficult to manufacture thin sheets. In addition, chemical treatment properties and the toughness of the weldment deteriorate. For this reason, the Si content should be 2.5% or less. From the perspective of ensuring chemical treatment properties and the toughness of the material and weldment, it is preferable that the Si content be less than 2.0%. From the perspective of ensuring the toughness of the weldment, it is preferable that the Si content be 1.8% or less, and more preferable that it be 1.5% or less.

[0089] Mn : 1.5 ∼ 3.5 %

[0090] Mn is an important element from the perspective of securing strength by obtaining tempered martensite and / or bainite with a specified area percentage, from the perspective of improving ductility by stabilizing residual γ through lowering the Ms point of residual γ, and from the perspective of improving ductility by suppressing the formation of carbides in bainite, similar to Si. To obtain these effects, the Mn content is set to 1.5% or more. From the perspective of stabilizing residual γ to improve ductility, it is preferable to set the Mn content to 2.5% or more. The Mn content is preferably 2.6% or more, and more preferably 2.7% or more. If the Mn content exceeds 3.5%, it becomes difficult to secure high ductility because the bainite transformation is significantly delayed. Furthermore, if the Mn content exceeds 3.5%, it becomes difficult to suppress the formation of massive coarse γ or massive coarse martensite, and the elongation flange formability also deteriorates. Accordingly, the Mn content is 3.5% or less. From the perspective of promoting bainite transformation to ensure high ductility, it is desirable to have a Mn content of 3.2% or less. More preferably, the Mn content is 3.1% or less.

[0091] P: 0.02% or less

[0092] P is an element that strengthens steel, but if its content is high, it degrades spot weldability. Therefore, the P content should be 0.02% or less. From the perspective of improving spot weldability, it is desirable to keep the P content 0.01% or less. In addition, although it is not necessary to include P, it is desirable to keep the P content 0.001% or more from the perspective of manufacturing costs.

[0093] S: 0.01% or less

[0094] S is an element that improves scale peelability during hot rolling and suppresses nitriding during annealing, but it reduces spot weldability, bendability, and hole expansion. For these reasons, the S content is set to 0.01% or less. In the present invention, spot weldability is prone to deterioration due to the high content of C, Si, and Mn; therefore, from the perspective of improving spot weldability, it is preferable to set the S content to 0.0020% or less, and more preferable to set it to less than 0.0010%. Additionally, although it is not necessary to include S, it is preferable to set the S content to 0.0001% or more from the perspective of manufacturing costs. More preferably, the S content is 0.0005% or more.

[0095] sol.Al: Less than 1.0%

[0096] Al is included for the purpose of deoxidation and to stabilize residual γ as a substitute for Si. Although a lower limit for sol.Al is not specifically specified, it is desirable to have a sol.Al content of 0.005% or more to perform stable deoxidation. Furthermore, it is more desirable to have a sol.Al content of 0.01% or more. On the other hand, if the sol.Al content becomes 1.0% or more, the strength of the material decreases drastically and adversely affects chemical treatment properties; therefore, the sol.Al content is kept below 1.0%. To obtain high strength, it is more desirable to keep the sol.Al content below 0.50%, and even more desirable to keep it below 0.20%.

[0097] N: Less than 0.015%

[0098] N is an element that forms nitrides such as BN, AlN, and TiN in steel, and it is an element that reduces the hot ductility of steel and degrades surface quality. In addition, in steel containing B, there is a harmful effect in that the benefits of B are lost through the formation of BN. If the N content is 0.015% or more, the surface quality deteriorates significantly. Therefore, the N content is kept below 0.015%. The N content is preferably 0.010% or less. Furthermore, although it is not necessary to contain N, it is preferable to have an N content of 0.0001% or more for the sake of manufacturing costs. More preferably, the N content is 0.001% or more.

[0099] The remainder other than the above is Fe and unavoidable impurities. It is preferable that the steel sheet of the present invention has a composition in which the above basic components are contained, and the remainder consists of iron (Fe) and unavoidable impurities.

[0100] The composition of the steel plate of the present invention may appropriately contain, in addition to the above components, one or more of the following optional elements selected from (A), (B), and (C).

[0101] (A) One or two types selected from Ti: 0.1% or less and B: 0.01% or less in mass%

[0102] (B) in mass%, one or more selected from Cu: 1% or less, Ni: 1% or less, Cr: 1.0% or less, Mo: 0.5% or less, V: 0.5% or less, Nb: 0.1% or less, Zr: 0.2% or less, and W: 0.2% or less.

[0103] (C) In mass%, one or more selected from Ca: 0.0040% or less, Ce: 0.0040% or less, La: 0.0040% or less, Mg: 0.0030% or less, Sb: 0.1% or less, and Sn: 0.1% or less.

[0104] Ti: 0.1% or less

[0105] Ti acts to fix N in the steel as TiN, thereby improving hot ductility and enhancing the quenchability of B. Additionally, it has the effect of refining the microstructure through the precipitation of TiC. To obtain these effects, it is desirable to have a Ti content of 0.002% or more. From the perspective of sufficiently fixing N, it is more desirable for the Ti content to be 0.008% or more. Even more preferably, the Ti content is 0.010% or more. On the other hand, if the Ti content exceeds 0.1%, it may lead to an increase in rolling load and a decrease in ductility due to an increase in precipitation strengthening. For this reason, when Ti is included, the Ti content is kept at 0.1% or less. Preferably, the Ti content is 0.05% or less. To ensure high ductility, it is more desirable to keep the Ti content at 0.03% or less.

[0106] B: 0.01% or less

[0107] B is an element that improves the quenchability of steel and facilitates the formation of tempered martensite and / or bainite with a predetermined area percentage. Additionally, the presence of solid solution B improves resistance to delayed fracture. To obtain such effects of B, it is desirable to have a B content of 0.0002% or more. Furthermore, it is more desirable to have a B content of 0.0005% or more. Even more preferably, the B content is 0.0010% or more. On the other hand, if the B content exceeds 0.01%, not only is the effect saturated, but it also causes a significant decrease in hot ductility and generates surface defects. Therefore, when B is included, the B content is kept at 0.01% or less. Preferably, the B content is 0.0050% or less. More preferably, the B content is 0.0030% or less.

[0108] Cu: 1% or less

[0109] Cu improves corrosion resistance in the operating environment of automobiles. Additionally, corrosion products of Cu can coat the surface of the steel sheet, thereby suppressing hydrogen intrusion into the steel sheet. Cu is an element incorporated when scrap is utilized as a raw material; by allowing the incorporation of Cu, recycled materials can be utilized as raw materials, and manufacturing costs can be reduced. From this perspective, it is desirable to contain 0.005% or more of Cu, and from the perspective of improving delayed fracture resistance, it is more desirable to contain 0.05% or more of Cu. Even more preferably, the Cu content is 0.10% or more. On the other hand, if the Cu content becomes excessively high, it leads to the occurrence of surface defects. For this reason, when Cu is included, the Cu content is kept at 1% or less. The Cu content is preferably 0.4% or less, and more preferably 0.2% or less.

[0110] Ni: 1% or less

[0111] Ni, like Cu, can improve corrosion resistance. Additionally, Ni can suppress the occurrence of surface defects that are prone to occur when Cu is included. For these reasons, it is desirable to include 0.01% or more of Ni. The Ni content is more preferably 0.04% or more, and even more preferably 0.06% or more. On the other hand, if the Ni content becomes excessively high, scale formation within the furnace becomes uneven and instead causes surface defects. It also leads to increased costs. For this reason, when Ni is included, the Ni content is kept at 1% or less. The Ni content is preferably 0.4% or less, and more preferably 0.2% or less.

[0112] Cr: 1.0% or less

[0113] Cr may be included for the effect of improving the quenchability of steel and suppressing the formation of carbides in martensite or upper / lower bainite. To obtain these effects, it is preferable that the Cr content be 0.01% or more. More preferably, the Cr content is 0.03% or more, and even more preferably 0.06% or more. On the other hand, if Cr is included in excess, pitting corrosion resistance deteriorates. For this reason, when Cr is included, the Cr content is kept at 1.0% or less. The Cr content is preferably 0.8% or less, and more preferably 0.4% or less.

[0114] Mo: 0.5% or less

[0115] Mo may be included for the effect of improving the quenchability of steel and suppressing the formation of carbides in martensite or upper / lower bainite. To obtain these effects, it is preferable to have a Mo content of 0.01% or more. More preferably, the Mo content is 0.03% or more, and even more preferably 0.06% or more. On the other hand, Mo significantly deteriorates the chemical treatment properties of cold-rolled steel sheets. For this reason, when Mo is included, the Mo content is kept at 0.5% or less. From the perspective of improving chemical treatment properties, it is preferable to keep the Mo content at 0.15% or less.

[0116] V: 0.5% or less

[0117] V may be included for the effect of improving the quenchability of steel, the effect of suppressing the formation of carbides in martensite or upper / lower bainite, the effect of refining the microstructure, and the effect of improving delayed fracture resistance by precipitating carbides. To obtain these effects, it is preferable that the V content be 0.003% or more. The V content is more preferably 0.005% or more, and even more preferably 0.010% or more. On the other hand, if V is contained in large amounts, castability deteriorates significantly. For this reason, when V is included, the V content is set to 0.5% or less. The V content is preferably 0.3% or less, and more preferably 0.1% or less. The V content is even more preferably 0.05% or less, and even more preferably 0.03% or less.

[0118] Nb: 0.1% or less

[0119] Nb may be included for the effects of refining the steel structure to increase strength, promoting bainite transformation through grain refinement, improving bendability, and enhancing delayed fracture resistance. To obtain these effects, it is preferable to have an Nb content of 0.002% or more. More preferably, the Nb content is 0.004% or more, and even more preferably 0.010% or more. On the other hand, if Nb is included in large amounts, precipitation strengthening becomes excessively strong, leading to a decrease in ductility. It also results in an increase in rolling load and a deterioration in castability. For this reason, when Nb is included, the Nb content is kept at 0.1% or less. The Nb content is preferably 0.05% or less, and more preferably 0.03% or less.

[0120] Zr: 0.2% or less

[0121] Zr may be included for the effect of improving the quenchability of steel, suppressing the formation of carbides in bainite, refining the microstructure, and improving delayed fracture resistance by precipitating carbides. To obtain such effects, it is desirable to have a Zr content of 0.005% or more. More preferably, the Zr content is 0.008% or more, and even more preferably 0.010% or more. On the other hand, if Zr is contained in large amounts, coarse precipitates such as ZrN or ZrS, which remain undissolved during slab heating before hot rolling, increase, and delayed fracture resistance deteriorates. For this reason, when Zr is included, the Zr content is kept at 0.2% or less. The Zr content is preferably 0.15% or less, and more preferably 0.08% or less. The Zr content is even more preferably 0.03% or less, and even more preferably 0.02% or less.

[0122] W: 0.2% or less

[0123] W may be included for the effect of improving the quenchability of the steel, the effect of suppressing the formation of carbides in bainite, the effect of refining the microstructure, and the effect of improving delayed fracture resistance by precipitating carbides. To obtain such effects, it is preferable that the W content be 0.005% or more. The W content is more preferably 0.008% or more, and even more preferably 0.010% or more. On the other hand, if a large amount of W is included, coarse precipitates such as WN or WS that remain undissolved during slab heating before hot rolling increase, and the delayed fracture resistance deteriorates. For this reason, when W is included, the W content is kept at 0.2% or less. The W content is preferably 0.15% or less, and more preferably 0.08% or less. The W content is even more preferably 0.03% or less, and even more preferably 0.02% or less.

[0124] Ca: 0.0040% or less

[0125] Ca fixes S as CaS and contributes to the improvement of bendability and delayed fracture resistance. For this reason, it is desirable to have a Ca content of 0.0002% or more. More preferably, the Ca content is 0.0005% or more, and even more preferably 0.0010% or more. On the other hand, adding a large amount of Ca degrades surface quality or bendability. For this reason, when Ca is included, the Ca content is kept at 0.0040% or less. The Ca content is preferably 0.0035% or less, and more preferably 0.0020% or less.

[0126] Ce: 0.0040% or less

[0127] Ce, like Ca, fixes S and contributes to the improvement of bendability and delayed fracture resistance. For this reason, it is desirable to have a Ce content of 0.0002% or more. More preferably, the Ce content is 0.0004% or more, and even more preferably 0.0006% or more. On the other hand, adding a large amount of Ce degrades surface quality or bendability. For this reason, when Ce is included, the Ce content is kept at 0.0040% or less. The Ce content is preferably 0.0035% or less, and more preferably 0.0020% or less.

[0128] La : 0.0040 % or less

[0129] La, like Ca, fixes S and contributes to the improvement of bendability and delayed fracture resistance. For this reason, it is desirable to have a La content of 0.0002% or more. More preferably, the La content is 0.0004% or more, and even more preferably 0.0006% or more. On the other hand, adding a large amount of La degrades surface quality or bendability. For this reason, when La is included, the La content is kept at 0.0040% or less. The La content is preferably 0.0035% or less, and more preferably 0.0020% or less.

[0130] Mg: 0.0030% or less

[0131] Mg fixes O as MgO and contributes to the improvement of delayed fracture resistance. For this reason, it is desirable to have an Mg content of 0.0002% or more. More preferably, the Mg content is 0.0004% or more, and even more preferably 0.0006% or more. On the other hand, adding a large amount of Mg degrades surface quality or bendability. For this reason, when Mg is included, the Mg content is kept at 0.0030% or less. The Mg content is preferably 0.0025% or less, and more preferably 0.0010% or less.

[0132] Sb: 0.1% or less

[0133] Sb inhibits oxidation or nitridation of the surface layer of the steel sheet and inhibits the reduction of the content of C or B in the surface layer caused by such inhibition. Furthermore, by inhibiting the aforementioned reduction of the content of C or B, the formation of ferrite in the surface layer of the steel sheet is inhibited, thereby increasing strength and improving delayed fracture resistance. From this perspective, it is preferable that the Sb content be 0.002% or more. The Sb content is more preferably 0.004% or more, and even more preferably 0.006% or more. On the other hand, if the Sb content exceeds 0.1%, castability deteriorates, and it segregates at the old γ grain boundaries, deteriorating the delayed fracture resistance of the shear cross-section. Therefore, when Sb is included, the Sb content is kept at 0.1% or less. The Sb content is preferably 0.04% or less, and more preferably 0.03% or less.

[0134] Sn: 0.1% or less

[0135] Sn inhibits oxidation or nitridation of the surface layer of the steel sheet, thereby inhibiting the reduction of the content of C or B in the surface layer. Furthermore, by inhibiting the aforementioned reduction of the content of C or B, the formation of ferrite in the surface layer of the steel sheet is suppressed, resulting in increased strength and improved resistance to delayed fracture. From this perspective, it is preferable that the Sn content be 0.002% or more. The Sn content is preferably 0.004% or more, and more preferably 0.006% or more. On the other hand, if the Sn content exceeds 0.1%, castability deteriorates. In addition, Sn segregates at the spherical γ grain boundaries, deteriorating the resistance to delayed fracture of the shear cross-section. Therefore, when Sn is included, the Sn content is kept at 0.1% or less. The Sn content is preferably 0.04% or less, and more preferably 0.03% or less.

[0136] When the above-mentioned optional component is contained in an amount below a desirable lower limit, the optional element contained in an amount below the lower limit does not impede the effects of the present invention. Therefore, when the above-mentioned optional element is contained in an amount below the lower limit, the optional element is considered to be contained as an unavoidable impurity.

[0137] Next, the steel structure of the steel plate of the present invention will be described.

[0138] Polygonal ferrite: 10% or less (including 0%)

[0139] Polygonal ferrite generated during annealing or cooling contributes to the improvement of ductility, but causes a decrease in elongation flange formability due to a difference in hardness with surrounding hard phases such as martensite. Since the polygonal ferrite does not impair the effects of the present invention as long as the area percentage is 10% or less, it is acceptable for it to be included. Therefore, in the present invention, the polygonal ferrite is set to 10% or less in area percentage. The polygonal ferrite is preferably 5% or less, and more preferably 2% or less. In addition, the polygonal ferrite may be 0%.

[0140] Tempered Martensite: 30% or more

[0141] To obtain the desired strength and elongation flange formability, the tempered martensite is set to an area percentage of 30% or more. The tempered martensite is preferably 40% or more. On the other hand, if the tempered martensite exceeds 80%, ductility is reduced due to excessive high strength, so it is desirable to keep the tempered martensite at 80% or less. More preferably, the tempered martensite is 75% or less.

[0142] Fresh martensite: 20% or less (including 0%)

[0143] Conventionally, when attempting to induce a large amount of bainite transformation during the final tempering process (a process involving retention at an average cooling rate of CR4 as described below), a large amount of massive martensite or massive residual γ remains. Therefore, to prevent this, a method of reducing Mn to promote bainite transformation has been used in the past. However, reducing the Mn content resulted in the loss of the stabilization effect of residual γ and the effect of increasing volume fraction, thereby impairing ductility. In contrast, the present invention, which performs an appropriate cooling treatment on a steel plate containing a large amount of Mn, enables both the utilization of bainite transformation and the reduction of the massive structure.

[0144] Excellent elongation flange formability can be secured by reducing the area percentage of the bulk fresh martensite structure to 20% or less. Therefore, in the present invention, the fresh martensite is reduced to 20% or less in area percentage. To secure excellent elongation flange formability, it is preferable to reduce the fresh martensite to 10% or less. More preferably, the fresh martensite is 5% or less. In addition, the fresh martensite may be 0%.

[0145] Lower bainite: 5 ~ 50 %

[0146] The lower bainite formed during the residence time in the cooling process after annealing is more ductile than tempered martensite, so it contributes to improving the strength-ductility balance and also contributes to improving the work hardening index (n value). Since this effect is not sufficiently obtained when the amount of lower bainite is less than 5%, the amount of lower bainite is set to 5% or more. The lower bainite is preferably 10% or more. On the other hand, since strength decreases when the amount of lower bainite exceeds 50%, the amount of lower bainite is set to 50% or less. The lower bainite is preferably 40% or less.

[0147] Microstructure having one or more types of tempered martensite, fresh martensite, upper bainite, lower bainite, and retained austenite: 90% or more (including 100%)

[0148] In order to secure the specified strength, ductility, and elongation flange formability, the total area ratio of tempered martensite, fresh martensite, upper bainite, lower bainite, and retained austenite as the remainder structure of the above-mentioned polygonal ferrite is 90% or more. The remainder structure may be a structure having one or more of tempered martensite, fresh martensite, upper bainite, lower bainite, and retained austenite, or a structure consisting of one or more of tempered martensite, fresh martensite, upper bainite, lower bainite, and retained austenite.

[0149] Retained austenite: 5 ~ 20 %

[0150] To ensure high ductility, the volume percentage of retained austenite (retained γ) in the entire steel structure is 5% or more. The retained austenite is preferably 7% or more, and more preferably 9% or more. This amount of retained γ includes retained γ formed adjacent to bainite. If the amount of retained γ increases excessively, it leads to a decrease in strength, a decrease in elongation flange formability, and a deterioration in resistance to delayed fracture. Therefore, the volume percentage of retained γ is set to 20% or less. The retained austenite is preferably 15% or less. Furthermore, "volume percentage" can be considered as "area percentage."

[0151] Area S of the region where the C concentration is 0.50 % (mass%) or higher C≥0.5 a. Area S of the region where the concentration of C is 0.30 % (mass%) or higher C≥0.3 The ratio S in C≥0.5 / S C≥0.3 ×100 is 15% or more

[0152] To ensure high ductility, the area S of the region where the C concentration is 0.50% or higher C≥0.5 a, Area S of the region where the concentration of C is 0.30% or higher C≥0.3 The ratio S in C≥0.5 / S C≥0.3 ×100 is set to 15% or more. The above ratio is preferably 20% or more, and more preferably 25% or more.

[0153] Next, a method for measuring the steel structure of a steel plate according to the present invention will be described.

[0154] The measurement of the area percentages of polygonal ferrite, bainitic ferrite, tempered martensite, and fresh martensite is performed by cutting a cross-section of the plate thickness perpendicular to the steel plate surface and parallel to the rolling direction, mirror-polishing it, etching it with 3 vol% Nital, and observing 10 fields of view at a magnification of 5000x using SEM at the 1 / 4 thickness position. Figure 1 shows an example of an SEM image of the steel microstructure of the steel plate. Polygonal ferrite, as shown in Figure 1, refers to relatively equiaxial ferrite that contains almost no internal carbides. It is the region that appears darkest in the SEM. The total area percentage of tempered martensite and lower bainite is the area percentage S of the region containing a lath-shaped lower structure and carbide precipitation in the SEM. TM+LB Fresh martensite is a massive region that appears white in SEM, with no underlying structure visible inside.

[0155] Since lower bainite and tempered martensite are difficult to distinguish in SEM, they are measured by a formaster test as follows. Figure 2 is a diagram illustrating a formaster test to measure the area ratio of tempered martensite and lower bainite.

[0156] Using a cylindrical specimen (diameter 3 mm × height 10 mm), the change in height of the specimen was measured when heat treatment was performed under predetermined annealing conditions using a Formaster tester. During the cooling process after annealing, the expansion occurring in a process where the temperature range from the martensite transformation initiation temperature Ms to the residence cessation temperature T1 (°C) is maintained for a residence time t: between 5 s and 60 s with an average cooling rate CR2: 10 °C / s or less, indicates that the expansion due to martensite transformation is smaller than the expansion due to lower bainite transformation, so it can be considered to be almost entirely due to lower bainite transformation. As shown in Fig. 2, after considering the effect of thermal shrinkage due to cooling, the height change D due to lower bainite transformation LB Wow, height change D due to martensitic transformation and lower bainite transformation TM+LB Using, and also the total area ratio S of tempered martensite and lower bainite obtained by the aforementioned SEM observation TM+LB Using, the area ratio S of the lower bainite LB and area ratio S of tempered martensite TM It can be approximated by the following equation.

[0157] S LB = S TM+LB ×D LB / D TM+LB

[0158] S TM = S TM+LB -S LB

[0159] A structure having one or more types of tempered martensite, fresh martensite, upper bainite, lower bainite, and retained austenite corresponds to the remainder structure other than the polygonal ferrite described above, and the total area ratio of this structure is the area ratio of the region other than the polygonal ferrite described above. Here, since the area ratio of carbides is very small, it is included in the area ratio of the remainder structure described above.

[0160] The volume fraction of retained austenite (retained γ) is obtained by chemical polishing from the surface of the steel plate to a thickness of 1 / 4 and by X-ray diffraction. A Co-Kα source is used for the incident X-rays, and the volume fraction of retained austenite is calculated from the intensity ratio of the (200), (211), (220) planes of ferrite and the (200), (220), (311) planes of austenite. Here, since retained γ is randomly distributed, the volume fraction of retained γ obtained by X-ray diffraction is equivalent to the area fraction of retained γ in the steel structure.

[0161] Area S of the region where the C concentration is 0.50 % (mass%) or higher C≥0.5 and the area S of the region where the C concentration is 0.30 % (mass%) or higher C≥0.3 The measurement was performed using a Field Emission Electron Beam Microanalyzer (FE-EPMA) JXA-8500F manufactured by Nippon Electronics at a position 1 / 4 of the plate thickness of the cross-section perpendicular to the steel plate surface and parallel to the rolling direction, with an acceleration voltage of 6 kV and an irradiation current of 7×10 -8 A, measured by mapping and analyzing the concentration distribution of C with the beam diameter minimized.

[0162] However, to exclude the influence of contamination, a background amount is subtracted so that the average value of C obtained from the analysis becomes equal to the carbon content of the base material. That is, if the average value of the measured carbon content is greater than the carbon content of the base material, the increase is considered to be contamination, and the value obtained by uniformly subtracting that increase from the analysis value at each location is taken as the true C amount at each location.

[0163] The steel plate of the present invention preferably has a tensile strength of 980 MPa or higher. More preferably, it is 1180 MPa or higher. Regarding the upper limit of tensile strength, it is preferably 1450 MPa or lower from the perspective of compatibility with other properties, and more preferably 1400 MPa or lower.

[0164] In the steel sheet of the present invention, the forming stability is particularly improved by ensuring that the full elongation T-El is 16.0% or more for TS: less than 1180 MPa, 14.0% or more for TS: 1180 MPa or more and less than 1320 MPa, and 13.0% or more for TS: 1320 MPa or more. It is preferable to ensure that the hole expansion rate λ is 30% or more. From the perspective of compatibility with other characteristics, the upper limit of λ is preferably 90% or less at any strength level, and more preferably 80% or less.

[0165] In the steel sheet of the present invention, it is preferable that the work hardening index n value is 0.130 or higher for TS: less than 1180 MPa, 0.070 or higher for TS: 1180 MPa or higher but less than 1320 MPa, and 0.060 or higher for TS: 1320 MPa or higher.

[0166] The steel sheet of the present invention described above may be a steel sheet having a zinc plating layer on its surface. The plating layer may be either a hot-dip plating layer or an electroplating layer.

[0167] Next, the method for manufacturing the steel plate of the present invention will be described.

[0168] In the method for manufacturing a steel sheet according to the present invention, after performing hot rolling and cold rolling on a steel slab having the aforementioned compositional composition, annealing is performed on the obtained cold-rolled steel sheet, wherein the annealing comprises a process of holding at an annealing temperature of 810 to 900 ℃, a process of cooling at an average cooling rate (CR1) of 5 to 100 ℃ / s within a temperature range from 810 ℃ to a martensitic transformation start temperature Ms (℃), a process of holding at a residence time t of 5 s or more and 60 s or less at an average cooling rate (CR2) of 10 ℃ / s or less within a temperature range from the martensitic transformation start temperature Ms (℃) to a residence stop temperature (T1) of Ms-100 to Ms-10 (℃), and a cooling stop temperature (T2) of 180 ℃ or more and less than 290 ℃ from the residence stop temperature (T1). The process includes, in this order, a process of cooling a temperature range up to 380°C at an average cooling rate (CR3): 3 to 100°C / s; a process of heating a temperature range from the cooling stop temperature (T2) to 380°C at an average heating rate: 2°C / s or more; a process of maintaining the temperature range from 340°C to 590°C for 20 s to 3000 s at an average cooling rate (CR4): 0.01 to 5°C / s; and a process of cooling to a temperature of 50°C or lower at an average cooling rate (CR5): 0.1°C / s or more.

[0169] In addition, the temperature specified in each process of the present invention refers to the surface temperature of the slab (steel slab) or steel plate.

[0170] In addition, FIG. 3 is a drawing for explaining the method of manufacturing a steel plate according to the present invention, and in particular, shows the time change of the surface temperature of a slab (steel slab) or a steel plate. Details of each process, including this time change of temperature, will be explained below.

[0171] Hot rolling

[0172] To hot roll a steel slab, methods include heating the slab before rolling, rolling the slab directly without heating after continuous casting, or performing a short-term heat treatment on the slab after continuous casting before rolling. Hot rolling can be carried out according to conventional methods; for example, the slab heating temperature should be 1100 to 1300 ℃, the cracking time 20 to 300 min, the finish rolling temperature should be Ar3 transformation point to Ar3 transformation point + 200 ℃, and the coiling temperature 400 to 720 ℃. From the perspective of suppressing plate thickness variation and stably securing high strength, it is preferable to set the coiling temperature to 430 to 530 ℃.

[0173] Cold rolling

[0174] In cold rolling, the rolling reduction rate (cumulative rolling reduction rate) should be 30 to 85%. From the perspective of stably securing high strength and reducing anisotropy, it is desirable to set the rolling reduction rate to 35 to 85%. In addition, when the rolling load is high, it is possible to perform a softening annealing treatment by CAL (Continuous Annealing Line) or BAF (Box Annealing Furnace) at 450 to 730°C.

[0175] annealing

[0176] After hot rolling and cold rolling a steel slab having the aforementioned compositional components, annealing is performed under the conditions specified below. The annealing equipment is not particularly limited, but from the perspective of securing productivity and the desired heating and cooling rates, it is preferable to perform the annealing using a continuous annealing line (CAL) or a continuous hot-dip galvanizing line (CGL).

[0177] Annealing temperature: Maintain at 810–900°C

[0178] To obtain tempered martensite and / or bainite of a predetermined area percentage and residual γ of a predetermined volume percentage, the annealing temperature is set to 810 to 900 °C. To keep polygonal ferrite content at 5% or less, it is desirable to adjust the annealing temperature to ensure γ single-phase annealing. Preferably, it is 815 °C or higher. On the other hand, if the annealing temperature exceeds 900 °C, the γ grain size becomes excessively large, and the ductility decreases as the diffusion distance of C atoms required to obtain residual γ of the desired carbon concentration becomes longer. Therefore, the annealing temperature is set to 900 °C or lower. Preferably, the annealing temperature is 880 °C or lower.

[0179] Cooling the temperature range from 810 ℃ to the martensitic transformation onset temperature (Ms) (℃) at an average cooling rate (CR1) of 5 to 100 ℃ / s

[0180] After holding at 810 to 900 ℃, the temperature range from 810 ℃ to the martensite transformation initiation temperature Ms is cooled at an average cooling rate (CR1): 5 to 100 ℃ / s. If the average cooling rate (CR1) is slower than 5 ℃ / s, a large amount of ferrite is generated, resulting in reduced strength and reduced elongation flange formability. The average cooling rate (CR1) is preferably 8 ℃ / s or higher. On the other hand, if the average cooling rate becomes excessively fast, the plate shape deteriorates, so it is set to 100 ℃ / s or lower. The average cooling rate (CR1) is preferably 50 ℃ / s or lower, and more preferably less than 30 ℃ / s.

[0181] Here, the average cooling rate (CR1) is “(810 ℃ (cooling start temperature) – martensite transformation start temperature Ms (cooling stop temperature)) / (cooling time (seconds) from the cooling start temperature of 810 ℃ to the martensite transformation start temperature Ms (cooling stop temperature))”.

[0182] In addition, the martensite transformation initiation temperature Ms (°C) can be determined by using a formatronic tester to measure the volume change when a cylindrical test specimen (diameter 3 mm × height 10 mm) is held at a predetermined annealing temperature and then rapidly cooled with helium gas.

[0183] Martensitic transformation initiation temperature Ms, residence stop temperature (T1): temperature range from Ms-100 to Ms-10 (°C), average cooling rate (CR2): 10°C / s or less, residence time t: 5 s or more and 60 s or less.

[0184] By maintaining the temperature range from the martensite transformation initiation temperature Ms (°C) to the residence stop temperature (T1): Ms-100 ∼ Ms-10 (°C) for a residence time t: 5 s ≤ 60 s ≤ average cooling rate (CR2): 10 °C / s ≤ or less (slow cooling), it is possible to generate some martensite and then generate bainite using the martensite as a nucleus. Furthermore, due to the acceleration of bainite transformation by the swing back effect, it is possible to efficiently generate a predetermined amount of lower bainite in a short period of time. If the average cooling rate (CR2) exceeds 10 °C / s, the amount of bainite transformation decreases. Therefore, the average cooling rate (CR2) is set to 10 °C / s ≤ or less. If the residence time is less than 5 s, the desired amount of bainite is not obtained, and if it exceeds 60 s, the enrichment of C from bainite to the massive untransformed γ proceeds, resulting in an increase in the amount of residual massive structure. Therefore, the residence time is set to be between 5 s and 60 s. From the perspective of securing bainitic ferrite and retained austenite to improve ductility, it is desirable for the residence time to be 10 s or more. In addition, from the perspective of improving λ by reducing the massive structure, it is desirable for the residence time to be 50 s or less.

[0185] In addition, the martensite transformation initiation temperature Ms (°C), residence stop temperature (T1), average cooling rate (CR2), and residence time t (s) satisfy the following equation (1).

[0186] T1 = Ms-CR2×t … Equation (1)

[0187] That is, the average cooling rate (CR2) is “(martensite transformation start temperature Ms (°C) (residence start temperature) - residence stop temperature (T1)) / (residence time t (sec) from martensite transformation start temperature Ms (°C) to residence stop temperature T1)”.

[0188] Cooling the temperature range from the above residence stop temperature (T1) to the cooling stop temperature (T2) of 180°C or higher and less than 290°C at an average cooling rate (CR3): 3 to 100°C / s

[0189] After the above retention, it is necessary to cool rapidly to prevent excessive enrichment of carbon into γ. If the average cooling rate (CR3) in the temperature range from the retention stop temperature T1 to the cooling stop temperature T2 (180°C or higher and less than 290°C) is less than 3°C / s, the carbon is enriched into massive, untransformed γ, and the amount of fresh martensite at final cooling increases, thereby reducing the formability of the elongated flange. Therefore, from the perspective of improving the formability of the elongated flange, the average cooling rate (CR3) is set to 3°C / s or higher. The average cooling rate (CR3) is more preferably 5°C / s or higher, and even more preferably 8°C / s or higher. Since the plate shape deteriorates if the average cooling rate in this temperature range becomes excessively large, the average cooling rate (CR3) is set to 100°C / s or lower. The average cooling rate (CR3) is preferably 50°C / s or lower. To secure a predetermined amount of residual γ, the cooling stop temperature is set to 180°C or higher. The cooling stop temperature is preferably 200°C or higher, and more preferably 220°C or higher. If the cooling stop temperature is 290°C or higher, a large amount of bulk untransformed γ remains, and the amount of fresh martensite at final cooling increases, thereby reducing the formability of the elongated flange. Therefore, the cooling stop temperature is set to less than 290°C. The cooling stop temperature is preferably 280°C or lower.

[0190] Here, the average cooling rate (CR3) is “(retention stop temperature (T1))-(cooling stop temperature (T2) (°C)) / (cooling time from retention stop temperature (T1) to cooling stop temperature (T2) (seconds))”.

[0191] Temperature range from cooling stop temperature (T2) to 380°C, heated at an average heating rate of 2°C / s or more

[0192] In addition, high ductility can be secured by suppressing carbide precipitation by heating in a short time within the temperature range from the cooling stop temperature (T2) to 380°C. Furthermore, when reheating to 380°C or higher using martensite or bainite generated by cooling as a nucleus, bainite is formed. If the average heating rate to 380°C is slow, these effects are not obtained. As a result, the amount of residual γ decreases, and ductility is reduced. For this reason, the average heating rate within the temperature range from the cooling stop temperature (T2) to 380°C is set to 2°C / s or higher. From the perspective of suppressing carbide precipitation and generating bainite upon reheating, it is preferable to set the average heating rate to 5°C / s or higher, and more preferable to set it to 10°C / s or higher. The upper limit of the average heating rate is not particularly limited, but it is preferable to be 50°C / s or lower, and more preferably 30°C / s or lower.

[0193] Here, the average heating rate is “380 ℃ (heating stop temperature) - (cooling stop temperature (T2)) / (heating time (seconds) from cooling stop temperature (T2) to 380 ℃ (heating stop temperature))”.

[0194] Temperature range between 340 ℃ and 590 ℃, average cooling rate (CR4): 0.01 to 5 ℃ / s, retention time between 20 s and 3000 s

[0195] From the perspective of stabilizing residual γ by distributing C to it, and from the perspective of improving elongation flange formability by subdividing the region distributed as massive untransformed γ through bainite transformation, the material is held (slow cooling) for 20 s to 3000 s in a temperature range of 340 ℃ to 590 ℃. In addition, to suppress the formation of massive structures caused by the distribution of excess C to residual γ and to improve elongation flange formability through the self-tempering of fresh martensite, this temperature range is cooled slowly at an average cooling rate (CR4) of 0.01 to 5 ℃ / s. If the average cooling rate (CR4) is less than 0.01 ℃ / s, excess C is distributed to the residual γ, leading to a decrease in elongation flange formability due to the formation of massive structures. Therefore, the average cooling rate (CR4) is set to 0.01 ℃ / s or higher. Meanwhile, if the average cooling rate (CR4) exceeds 5 ℃ / s, the distribution of C to the residual γ is suppressed, and a sufficient amount of C enrichment region cannot be obtained. In addition, fresh martensite is formed, leading to the deterioration of λ. Therefore, the average cooling rate (CR4) is set to 5 ℃ / s or less.

[0196] Here, the average cooling rate (CR4) is “(cooling start temperature (T3) (°C))-(cooling stop temperature (T4) (°C)) / (cooling time (seconds) from cooling start temperature (T3) (°C) to cooling stop temperature (T4) (°C))”.

[0197] Here, the cooling start temperature (T3) and the cooling stop temperature (T4) are not particularly limited as long as they are in the range of 340°C or higher to 590°C, but it is preferable that the cooling start temperature (T3) be in the range of 360°C to 580°C and the cooling stop temperature (T4) be in the range of 350°C to 450°C.

[0198] In addition, holding (retention) in the temperature range of 340 to 590°C may be combined with hot-dip galvanizing treatment. That is, in the process of holding at the aforementioned average cooling rate (CR4): 0.01 to 5°C / s, hot-dip galvanizing treatment or alloying hot-dip galvanizing treatment may be performed on the steel plate. When performing hot-dip galvanizing treatment, it is preferable to immerse the steel plate in a galvanizing bath at a temperature of 440°C or higher and 500°C or lower to perform the hot-dip galvanizing treatment, and then adjust the plating adhesion amount by gas wiping, etc. For hot-dip galvanizing, it is preferable to use a galvanizing bath with an Al content of 0.10% or higher and 0.22% or lower. Furthermore, as alloying hot-dip galvanizing treatment, alloying treatment of the galvanizing may be performed after the hot-dip galvanizing treatment. When performing alloying treatment of the galvanizing, it is preferable to perform it in the temperature range of 470°C or higher and 590°C or lower.

[0199] In addition, this process is a process that performs cooling (retention, complete cooling), but if the above temperature range, residence time range, and average cooling rate CR4 range are satisfied, hot-dip galvanizing treatment or alloying treatment of galvanizing can be performed during this process. Hot-dip galvanizing treatment or alloying treatment of galvanizing may be accompanied by a temperature rise.

[0200] Average cooling rate to temperatures below 50 ℃ (CR5): Cooling at 0.1 ℃ / s or higher

[0201] Afterwards, cooling is performed at an average cooling rate (CR5) of 0.1 ℃ / s or more to a temperature of 50 ℃ or lower in order to prevent softening due to excessive tempering or a decrease in ductility due to carbide precipitation. Skin pass rolling can be performed on the steel sheet in order to stabilize press formability, such as adjusting surface roughness and flattening the plate shape, or to increase YS. It is preferable to set the skin pass elongation to 0.1 to 0.5%. In addition, it is also possible to flatten the plate shape using a leveler. The above-mentioned average cooling rate (CR5) to a temperature of 50 ℃ or lower is preferably 5 ℃ / s or more, and more preferably 100 ℃ / s or less.

[0202] Here, the average cooling rate (CR5) is “(340 ℃ (cooling start temperature (℃)) - 50 ℃ or lower cooling stop temperature (℃)) / (cooling time from cooling start temperature to cooling stop temperature (seconds))”.

[0203] In order to improve the formability of the elongated flange, it is also possible to perform a low-temperature heat treatment at 100 to 300°C for 30 seconds to 10 days after the above heat treatment or after skin pass rolling. Through this treatment, hydrogen that has entered the steel sheet during the final cooling or the tempering or annealing of the martensite generated during skin pass rolling is released from the steel sheet. It is possible to reduce hydrogen to less than 0.1 ppm through the low-temperature heat treatment. In addition, it is also possible to perform electroplating. That is, after the process of cooling at an average cooling rate (CR5) of 0.1°C / s or higher as described above, an electro-galvanizing treatment may be performed on the steel sheet. After performing electroplating, it is preferable to perform the above low-temperature heat treatment in order to reduce hydrogen in the steel.

[0204] The steel plate of the present invention preferably has a plate thickness of 0.5 mm or more. In addition, it is preferable that the plate thickness be 2.0 mm or less.

[0205] Next, the component of the present invention and the method of manufacturing the same will be described.

[0206] The component of the present invention is formed by performing at least one of forming and joining processes on the steel plate of the present invention. In addition, the method for manufacturing the component of the present invention includes a process of forming the component by performing at least one of forming and joining processes on the steel plate of the present invention.

[0207] The steel plate of the present invention has a tensile strength of 980 MPa or higher, high ductility, excellent elongation flange formability, and a high work hardening index. Therefore, a member obtained using the steel plate of the present invention is also high strength and possesses high ductility, excellent elongation flange formability, and a high work hardening index compared to conventional high-strength members. Furthermore, using the member of the present invention enables weight reduction. Accordingly, the member of the present invention can be preferably used, for example, in vehicle body frame parts. The member of the present invention also includes welded joints.

[0208] For forming processes, general processing methods such as press forming may be used without restriction. Additionally, for joining processes, general welding methods such as spot welding and arc welding, as well as riveting and caulking joints, may be used without restriction.

[0209] Examples

[0210] Hereinafter, embodiments of the present invention will be described.

[0211] A cold-rolled steel sheet with a thickness of 1.4 mm having the compositional composition shown in Table 1 was treated under the annealing conditions shown in Table 2 to produce the steel sheet of the present invention and the steel sheet of the comparative example.

[0212] Each cold-rolled steel sheet was obtained by performing hot rolling (slab heating temperature: 1200 ℃, cracking time: 60 min, finish rolling temperature: 900 ℃, coiling temperature: 500 ℃) and cold rolling (rolling reduction rate (cumulative rolling reduction rate): 50 %) on a steel slab having the compositional composition shown in Table 1.

[0213] In Table 2, the martensite transformation initiation temperature Ms was determined by measuring the volume change when a cylindrical test specimen (diameter 3 mm × height 10 mm) was held at a predetermined annealing temperature and then rapidly cooled with helium gas using a formamaster tester.

[0214] Meanwhile, some steel sheets (cold-rolled steel sheets: CR) were made into hot-dip galvanized steel sheets (GI) by performing a hot-dip galvanizing treatment in a process in which they are kept at a temperature range of 340°C to 590°C for 20 seconds to 3000 seconds at an average cooling rate of 0.01 to 5°C / s. Here, the steel sheets were immersed in a galvanizing bath at a temperature of 440°C to 500°C to perform hot-dip galvanizing treatment, and subsequently, the amount of plating deposited was adjusted by gas wiping, etc. For the hot-dip galvanizing, a galvanizing bath with an Al content of 0.10% to 0.22% was used. In addition, some hot-dip galvanized steel sheets were made into alloyed hot-dip galvanized steel sheets (GA) by performing an alloying treatment after the above hot-dip galvanizing treatment as an alloying hot-dip galvanizing treatment. Here, the alloying treatment was performed in a temperature range of 460°C to 590°C. In addition, some steel sheets (cold-rolled steel sheets: CR) were electroplated to become electro-galvanized steel sheets (EG).

[0215] Measurements of the bone tissue were performed using the following methods. The measurement results are shown in Table 3.

[0216] The measurement of the area percentages of polygonal ferrite, bainitic ferrite, tempered martensite, and fresh martensite is performed by cutting a cross-section of the plate thickness perpendicular to the steel plate surface and parallel to the rolling direction, mirror-polishing it, etching it with 3 vol% Nital, and observing 10 fields of view at a magnification of 5000x using SEM at the 1 / 4 thickness position. Polygonal ferrite, as shown in Fig. 1, was selected based on relatively equiaxial ferrite that contains almost no internal carbides. This is the region that appears darkest in the SEM. The total area percentage of tempered martensite and underlying bainite is the area percentage S of the region containing a lath-shaped underlying structure and carbide precipitation in the SEM. TM+LB Fresh martensite is a massive region that appears white in SEM, with no underlying structure visible inside.

[0217] Since lower bainite and tempered martensite are difficult to distinguish using SEM, they are measured by the Formaster test as follows. Using a cylindrical specimen (diameter 3 mm × height 10 mm), the change in height of the specimen was measured when heat treatment was performed under predetermined annealing conditions using a Formaster tester. During the cooling process after annealing, the expansion occurring in a process where the temperature range from the martensite transformation initiation temperature Ms to the residence cessation temperature T1 (°C) is maintained for a residence time t: between 5 s and 60 s with an average cooling rate CR2: 10 °C / s or less, indicates that the expansion due to martensite transformation is smaller than the expansion due to lower bainite transformation, so it can be considered almost entirely due to lower bainite transformation. As shown in Fig. 2, after considering the effect of thermal shrinkage due to cooling, the height change D due to lower bainite transformation LB Wow, height change D due to martensitic transformation and lower bainite transformation TM+LBUsing, and also the total area ratio S of tempered martensite and lower bainite obtained by the aforementioned SEM observation TM+LB Using, the area ratio S of the lower bainite LB and area ratio S of tempered martensite TM It was approximated by the following equation.

[0218] S LB = S TM+LB ×D LB / D TM+LB

[0219] S TM = S TM+LB -S LB

[0220] A structure having one or more types of tempered martensite, fresh martensite, upper bainite, lower bainite, and retained austenite corresponds to the remainder structure other than the polygonal ferrite described above, and the total area ratio of this structure is the area ratio of the region other than the polygonal ferrite described above. Here, since the area ratio of carbides is very small, it was included in the area ratio of the remainder structure described above.

[0221] The volume fraction of retained austenite (retained γ) was determined by X-ray diffraction after chemically polishing the steel plate to a thickness of 1 / 4 from the surface. A Co-Kα source was used for the incident X-rays, and the volume fraction of retained austenite was calculated from the intensity ratio of the (200), (211), (220) planes of ferrite and the (200), (220), (311) planes of austenite. Here, since retained γ is randomly distributed, the volume fraction of retained γ obtained by X-ray diffraction is equivalent to the area fraction of retained γ in the steel structure.

[0222] Area S of the region where the C concentration is 0.50 % (mass%) or higher C≥0.5 and the area S of the region where the C concentration is 0.30 % (mass%) or higher C≥0.3The measurement was performed using a Field Emission Electron Beam Microanalyzer (FE-EPMA) JXA-8500F manufactured by Nippon Electronics at a position 1 / 4 of the plate thickness of the cross-section perpendicular to the steel plate surface and parallel to the rolling direction, with an acceleration voltage of 6 kV and an irradiation current of 7×10 -8 A, C concentration distribution was measured by mapping analysis with the beam diameter minimized.

[0223] However, to exclude the influence of contamination, a background component was subtracted so that the average value of C obtained from the analysis became equivalent to the carbon content of the base material. That is, if the average value of the measured carbon content was greater than the carbon content of the base material, the increase was considered to be contamination, and the value obtained by uniformly subtracting that increase from the analysis value at each location was set as the true C amount at each location.

[0224] JIS No. 5 tensile test specimens were taken from the obtained steel plates, and tensile tests (in accordance with JIS Z2241) were performed. The tensile strength TS, full elongation T-El, and work hardening index n values ​​obtained from the tensile test are shown in Table 3. A tensile strength of 980 MPa or higher was judged to have excellent strength. In addition, a full elongation T-El of 16.0% or more for TS: less than 1180 MPa, 14.0% or more for TS: between 1180 MPa and less than 1320 MPa, and 13.0% or more for TS: 1320 MPa or higher was judged to have excellent ductility.

[0225] In addition, the work hardening index n value was calculated by a simplified method based on JIS Z2253, using two points where the nominal strain on the nominal stress-nominal strain curve is 2% and 5%. It was determined that a value of n of 0.130 or higher was used for TS: less than 1180 MPa, 0.070 or higher was used for TS: between 1180 MPa and 1320 MPa, and 0.060 or higher was used for TS: 1320 MPa or higher, indicating a high work hardening index.

[0226] In addition, the elongation flange formability was evaluated by a hole expansion test in accordance with the specifications of the Japan Steel Federation Standard JFST1001 on hole expansion test specimens taken from steel plates after heat treatment. Specifically, for each sample of size 100 mm × 100 mm, a punching tool with a punch diameter of 10 mm and a die diameter of 10.3 mm (clearance 13%) was used to punch, and then a conical punch with a tip angle of 60 degrees was used to ensure that the burr generated during the punching hole formation was on the outside, and hole expansion was performed until a crack penetrating the plate thickness occurred. At this time, d0 was defined as the initial hole diameter (mm) and d as the hole diameter at the time of crack occurrence (mm), and the hole expansion rate λ (%) was calculated as {(d-d0) / d0}×100 and is shown in Table 3. Steel having a λ of 30% or more was judged to have excellent hole expansion ability.

[0227] The examples of the present invention shown in Tables 2 and 3 have excellent strength, ductility, hole expandability, and work hardening index, whereas the comparative examples are inferior in all of these aspects.

[0228]

[0229]

[0230]

[0231] The present invention has very high ductility and excellent elongation flange formability, as well as a high work hardening index, and can be preferably applied for press forming used in automobiles, home appliances, etc., through a press forming process.

[0232] In addition, it was found that the member obtained by performing forming processing, the member obtained by performing joining processing, and the member obtained by performing forming processing and joining processing using the steel plate of the present invention example have high strength, high ductility, excellent elongation flange formability, and a high work hardening index, just like the steel plate of the present invention example, because the steel plate of the present invention example has high strength, high ductility, excellent elongation flange formability, and a high work hardening index.

Claims

Claim 1 It has a composition in mass% containing C: 0.06–0.25%, Si: 0.4–2.5%, Mn: 1.5–3.5%, P: 0.001–0.02%, S: 0.0001–0.01%, sol.Al: 0.005% or more and less than 1.0%, and N: 0.0001% or more and less than 0.015%, with the remainder being Fe and unavoidable impurities; in area percentage, polygonal ferrite: 10% or less (including 0%), tempered martensite: 30% or more, fresh martensite: 20% or less (including 0%), and lower bainite: 5–50%; and in volume percentage, residual A steel having a microstructure in which austenite is 5 to 20% and, by area percentage, one or more types other than polygonal ferrite—such as tempered martensite, fresh martensite, upper bainite, lower bainite, and retained austenite—area S of a region with a carbon concentration of 0.50% or more. C≥0.5 a, Area S of the region where the concentration of C is 0.30% or higher C≥0.3 The ratio S in C≥0.5 / S C≥0.3 Steel plate in which ×100 is 15% or more. Claim 2 A steel plate according to claim 1, wherein the above component composition further contains, in mass%, at least one of the following Group A, Group B, and Group C. Group A: One or two selected from Ti: 0.1% or less and B: 0.01% or less Group B: Cu: 1% or less, Ni: 1% or less, Cr: 1.0% or less, Mo: 0.5% or less, V: 0.5% or less, Nb: 0.1% or less, Zr: 0.2% or less, and W: 0.2% or less Group C: One or two or more selected from Ca: 0.0040% or less, Ce: 0.0040% or less, La: 0.0040% or less, Mg: 0.0030% or less, Sb: 0.1% or less, and Sn: 0.1% or less Claim 3 A steel plate having a zinc plating layer on its surface, as in claim 1. Claim 4 In claim 2, a steel plate having a zinc plating layer on its surface. Claim 5 A member formed by performing at least one of forming and joining processes on a steel plate described in any one of claims 1 to 4. Claim 6 A method for manufacturing a steel sheet as described in claim 1 or 2, wherein hot rolling and cold rolling are performed on a steel slab having the above compositional composition, and annealing is performed on the obtained cold-rolled steel sheet, wherein the annealing comprises: a process of holding at an annealing temperature of 810 to 900 ℃; a process of cooling at an average cooling rate CR1 of 5 to 100 ℃ / s within a temperature range from 810 ℃ to a martensitic transformation start temperature Ms (℃); a process of holding at a residence time t of 5 s or more and 60 s or less within a temperature range from the martensitic transformation start temperature Ms (℃) to a residence stop temperature T1 of Ms-100 (℃) to Ms-10 (℃) at an average cooling rate CR2 of 10 ℃ / s or less; and a cooling stop temperature T2 of 180 ℃ or more and less than 290 ℃ from the residence stop temperature T1. A method for manufacturing a steel sheet, comprising: a process of cooling a temperature range up to at an average cooling rate CR3: 3 to 100 ℃ / s; a process of heating a temperature range from the cooling stop temperature T2 to 380 ℃ at an average heating rate: 2 ℃ / s or more; a process of retaining the temperature within a temperature range from 340 ℃ to 590 ℃ for a period of 20 s to 3000 s at an average cooling rate CR4: 0.01 to 5 ℃ / s; and a process of cooling to a temperature of 50 ℃ or lower at an average cooling rate CR5: 0.1 ℃ / s or more. Claim 7 A method for manufacturing a steel plate according to claim 6, wherein, in a process of maintaining the steel plate at an average cooling rate CR4: 0.01 to 5 ℃ / s, a hot-dip galvanizing treatment or an alloyed hot-dip galvanizing treatment is performed on the steel plate. Claim 8 A method for manufacturing a steel plate according to claim 6, comprising a process of performing electro-galvanizing treatment on the steel plate after a process of cooling at an average cooling rate CR5: 0.1 ℃ / s or higher. Claim 9 A method for manufacturing a member, comprising a process of forming a member by performing at least one of forming processing and joining processing on a steel plate described in any one of claims 1 to 4. Claim 10 delete

Citation Information

Patent Citations

  • High-strength steel sheet and method for manufacturing same

    KR1020180099876A

  • High-strength hot-dip galvanized steel sheet and its manufacturing method

    KR1020210095189A

  • High strength cold rolled steel sheet for automotive use

    WO2018096090A1

  • High-strength hot-dip galvanized steel sheet and method for manufacturing same

    WO2020136988A1